Using personalized prognosis in the treatment of relapsing multiple sclerosis: A practical guide - Van Wijmeersch, Bart; Hartung, Hans-Peter; Vermersch, Patrick; Pugliatti, Maura; Pozzilli, Carlo; Grigoriadis, Nikolaos; Alkhawajah, Mona; Airas, Laura; Linker, Ralf; Oreja-Guevara, Celia (Frontiers in Immunology, 2022)
The clinical course of multiple sclerosis (MS) is highly variable among patients, thus creating important challenges for the neurologist to appropriately treat and monitor patient progress. Despite some patients having apparently similar symptom severity at MS disease onset, their prognoses may differ greatly. To this end, we believe that a proactive disposition on the part of the neurologist to identify prognostic “red flags” early in the disease course can lead to much better long-term outcomes for the patient in terms of reduced disability and improved quality of life. Here, we present a prognosis tool in the form of a checklist of clinical, imaging and biomarker parameters which, based on consensus in the literature and on our own clinical experiences, we have established to be associated with poorer or improved clinical outcomes. The neurologist is encouraged to use this tool to identify the presence or absence of specific variables in individual patients at disease onset and thereby implement sufficiently effective treatment strategies that appropriately address the likely prognosis for each patient.